2017
DOI: 10.1186/s12882-017-0701-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum osteoprotegerin in prevalent hemodialysis patients: associations with mortality, atherosclerosis and cardiac function

Abstract: BackgroundTo assess whether serum osteoprotegerin (OPG) and/or fetuin-A predict mortality and cardiovascular (CV) morbidity and mortality in hemodialysis patients.MethodsMulticenter, observational, prospective study that included 220 hemodialysis patients followed up for up to 6 years. Serum OPG and fetuin-A levels were measured at baseline and their possible association with clinical characteristics, CV risk biomarkers, carotid ultrasonographic findings, as well as their association with overall and CV mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Collado et al [ 40 ] tried to assess whether serum OPG and/or fetuin-A predict mortality and CV morbidity and mortality in HD patients, as well as their association with atherosclerosis and/or vascular calcification and with cardiac structure and function. The presence of carotid atherosclerotic disease, defined by a pathological intima-media thickness and/or presence of carotid plaques with stenosis or calcified atherosclerotic plaques was associated with higher OPG levels but not with fetuin-A levels.…”
Section: Ckd-mbd and Cardiovascular Calcificationsmentioning
confidence: 99%
“…Collado et al [ 40 ] tried to assess whether serum OPG and/or fetuin-A predict mortality and CV morbidity and mortality in HD patients, as well as their association with atherosclerosis and/or vascular calcification and with cardiac structure and function. The presence of carotid atherosclerotic disease, defined by a pathological intima-media thickness and/or presence of carotid plaques with stenosis or calcified atherosclerotic plaques was associated with higher OPG levels but not with fetuin-A levels.…”
Section: Ckd-mbd and Cardiovascular Calcificationsmentioning
confidence: 99%
“…1 ). Seven studies 24, 26-28, 30-32 were included in a qualitative meta-analysis to assess the association of the circulating OPG level, as a categorical variable, with all-cause mortality. Seven studies 8-10, 15, 25, 27, 29 were included in a quantitative meta-analysis to assess the association of a 1 pmol/L increase in the circulating OPG level with all-cause mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies 24, 26-28, 30-32, which included a total of 1,934 patients, reported the adjusted HR of all-cause mortality for the highest OPG level group compared with the lower OPG level group. According to the qualitative meta-analysis, patients with the highest OPG levels had a significantly higher risk of all-cause mortality (adjusted HR, 1.88; 95% CI, 1.45 - 2.44) compared with patients with lower OPG levels, and low heterogeneity ( I ² = 25.7%, P = 0.233) was found among studies ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum OPG levels are elevated in patients with CKD and end-stage kidney disease, potentially in response to the strongly pro-calcific milieu [8,14]. Studies in dialyzed and nondialyzed patients with CKD have found that, like the general population, high serum OPG levels are associated with vascular calcification and all-cause and cardiovascular mortality [7,[15][16][17][18]. Short-term studies have found that serum OPG declines immediately after KT [19,20].…”
Section: Introductionmentioning
confidence: 99%